2010
DOI: 10.1049/iet-rsn.2009.0088
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of sea radar clutter spikes

Abstract: In recent times, considerable advances have been made on analysing low grazing angle radar sea clutter in the gigahertz frequency range. In this work, a set of coherent and polarimetric sea clutter data is analysed focusing on the statistical and spectral properties of the spikes, whatever is the physical phenomenon that generates them. Using three sea spike defining parameters, the spike amplitude, the minimum spike width and the minimum interval between spikes, it is possible to identify the spiking events f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 7 publications
0
30
0
1
Order By: Relevance
“…For the target that can be detected with high detection probability in no multipath environment, positive multipath effect on radar detection of the target is limited, whereas negative multipath effect on radar detection of the target may be severe. (4) The effect of multipath on radar detection performance weakens as the target height increases or the distance between radar and target decreases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the target that can be detected with high detection probability in no multipath environment, positive multipath effect on radar detection of the target is limited, whereas negative multipath effect on radar detection of the target may be severe. (4) The effect of multipath on radar detection performance weakens as the target height increases or the distance between radar and target decreases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the amplitude distribution of the radar sea clutter observed at low grazing angles approximately obeys K distribution [3][4][5]. Also, a number of investigations analysing the radar detection performance in K distributed clutter have appeared [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing simultaneous V and H polarized bistatic data, it would appear that when H pol is transmitted the corresponding bistatic co-polarized H data has lower percentage of spikes (node 1 data vs node 2 data for first seven experiments in Fig. 7a and 7d Figure 7 were obtained just by counting the spike events using a simple intensity threshold, without investigating other characteristics of the spike events such as duration and interval between spikes as in [37], or linking spike characteristics to parameters of amplitude and Doppler statistics to distinguish between different scattering mechanisms as in [35]. A more advanced analysis of spike events goes beyond the scope of this paper and will be covered in future work.…”
Section: Analysis Of Amplitude Statisticsmentioning
confidence: 99%
“…In [4], the authors propose a new method of modeling and simulation of temporal-spatial-correlated (TPC) clutter, based on the weighted norm in discrete complex linear space and a simple matrix transformation. In [5], the authors show a sample of results from a statistical and spectral analysis of a set of sea spikes selected from the radar returns, focusing on their Doppler properties, the spike duration and the temporal interval between spikes. In [6], a research in the area of bistatic radar clutter modeling is presented.…”
Section: Introductionmentioning
confidence: 99%